Prostatic artery embolization performed in anteroposterior projections versus steep oblique projections: single centre retrospective comparative analysis - Moschouris, Hippocrates (CVIR Endovasc, 2021)
BACKGROUND: To present and evaluate an approach for reduction of utilization of steep oblique angiographic projections during prostatic artery embolization (PAE). METHODS: Single-center, retrospective study of patients who underwent bilateral PAE (from October 2018 to November 2019) and in whom it was possible to embolize PA of at least one pelvic side utilizing anteroposterior projections only (AP-PAE group), with the following techniques: Identification of the origin of PA on anteroposterior angiographic views. Utilization of anatomic landmarks from the planning computed tomographic angiography. Distal advancement of the angiographic catheter or microcatheter in the anterior division of internal iliac artery. Gentle probing with microguidewire at the expected site of origin of the PA. The AP-PAE approach was initially applied to all PAE patients during the study period and when this approach failed, additional steep oblique projections were acquired; patients who underwent bilateral PAE, with both anteroposterior and oblique projections for both pelvic sides, formed the standard PAE (S-PAE) group. The AP-PAE group was compared with S-PAE group in terms of baseline clinical and anatomic features, technical/procedural aspects and outcomes. RESULTS: Forty-six patients (92 pelvic sides) were studied. AP-PAE was feasible in 12/46 patients (26.0%): unilateral AP-PAE in 9/46 patients (19.5%); bilateral AP-PAE in 3/46 patients (6.5%). AP-PAE group had larger prostates (p = 0.047) and larger PAs (p < 0.001). Body mass index (BMI) and other baseline features were comparable between the two groups (mean BMI, AP-PAE group: 27.9 ± 3.6, S-PAE group: 27.0 ± 3.5, p = 0.451). Mean fluoroscopy time and dose area product were lower in AP-PAE group (46.3 vs 57.9 min, p = 0.084 and 22,924.9 vs 35,800.4 μGy(.)m(2), p = 0.018, respectively). Three months post PAE, comparable clinical success rates (11/12 vs 31/34, p = 0.959) and mean International Prostate Symptom Score reduction (60.2% vs 58.1%, p = 0.740) were observed for AP-PAE and for S-PAE group, respectively. No major complications were encountered. CONCLUSION: AP-PAE is associated with significant reduction in radiation exposure and appears to be feasible, safe and effective, but it can be applied in a relatively small percentage of patients. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s42155-021-00209-7.